Pengaruh Pengetahuan Perpajakan, Sosialisasi Perpajakan, Kesadaran Wajib Pajak dan SAMSAT Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Kendal - Artin Milleani; Maryono (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Motor vehicle tax is a type of provincial tax in local taxes. In increasing regional income, motor vehicle taxpayer compliance plays an important role. The value of arrears in the Kendal Samsat shows that there is still a lack of compliance in paying taxes.This study aims to examine the effect of tax knowledge, tax socialization, awareness of taxpayers and mobile samsat on motor vehicle taxpayer compliance in Kendal Regency. The population and sample were carried out on taxpayers registered at SAMSAT Kendal and obtained 100 respondents using the formula solvin. Data collection uses a questionnaire with incidental sampling technique. Data analysis used multiple linear regression. The results showed that knowledge of taxation, socialization of taxation, awareness of taxpayers and mobile Samsat had a positive and significant effect on compliance with motorized vehicle taxpayers in Kendal Regency.